Motivasi Belajar Siswa dengan Metode Pembelajaran dalam Jaringan (Daring) di Masa Pandemi pada Mata Pelajaran PPKN - Hidayati Suhaili; Yuhasnil Yuhasnil; Sri Mulyani (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The aim of this research is to find out how students' learning motivation is and efforts to increase learning motivation with online methods during the pandemic in Pancasila and Citizenship Education subjects in class XI IPA SMA Negeri 1 Situjuah Limo Nigari District. The research method uses qualitative research using descriptive methods. Research informants were determined by purposive sampling and also collaborated with snowball sampling, which consisted of nine people. To ensure the validity of the data, triangulation was used. The results of the study show that student learning motivation in participating in online Civics learning during the pandemic has not been carried out optimally due to unsupportive conditions during the current pandemic, thus limiting interaction between students and teachers. Network conditions that do not support the online Civics learning process have caused many students to be constrained by not being able to participate in online Civics learning. The conclusion of the research is that teachers motivate students during online learning in the form of: (a). Giving praise, (b). Giving support, (c). Give a test, (d). Giving value or number, (e). Knowing the results, (f). Provide competition or competition, (g). Give punishment. Meanwhile, the efforts given by parents are in the form of: (a). Creating a supportive home climate, (b). Provide sufficient time, (c). Give awards. Keywords: Civics Learning (Online), Student Learning Motivation.